Modeling and analysis of 100 kW two-stage three-phase grid-connected PV generation system under absurd atmospheric and grid disturbances. - Muhammad Hafeez Mohamed Hariri; Mohamed Salem; Mohamad Kamarol Mohd Jamil; Mohamad Nazir Abdullah; Mohd Khairunaz Mat Desa (PLoS ONE, 2025)
The sustainable growth of renewable energy sources, especially photovoltaic (PV) driven electricity generation, is expected to grow exponentially over the next few years. The extraction of grid parameters such as the line voltage's magnitude, phase angle, and phase sequence, are crucial for the effective control of PV-grid synchronization. The existing grid synchronization technique such as a conventional phase-locked loop (PLL) is unable to provide an accurate fundamental frequency positive sequence under various types of grid fault conditions. Therefore, the main purpose of this article is to model and analyze the introduction of cascaded delay signal cancelation (CDSC) for a 100 kW two-stage three-phase grid-connected PV generation system under absurd atmospheric and various grid disturbances. The performance of the CDSC is benchmarked with a conventional structure of PLL as well as a double second-order generalized integrator (DSOGI). The modeling and analyses of these selected grid synchronizers were performed in a Matlab-Simulink (R2020b) environment.